High expression of FOXP3 in primary melanoma is associated with tumour progression. (1st January 2014) - Gerber, A.L.; Münst, A.; Schlapbach, C.; Shafighi, M.; Kiermeir, D.; Hüsler, R.; Hunger, R.E.
Summary: Background: The antitumour immune response plays an important role in the prognosis of melanoma. High numbers of circulating regulatory T cells have been associated with rapid disease progression. Objectives: To assess the influence of forkhead box protein (FOXP)3, CD1a and langerin expression on the prognosis of primary melanoma. Methods: We analysed 185 primary melanomas by immunohistochemical staining for expression of the regulatory T‐cell marker FOXP3 and the dendritic cell markers langerin and CD1a, and correlated marker expression with clinical outcome. Results: Disease‐free survival and overall survival were significantly longer in patients expressing low levels of FOXP3 in the primary melanoma, whereas they were associated with high expression of CD1a. The negative prognostic value of FOXP3 expression was independent of the Breslow tumour thickness. Langerin expression did not correlate with the clinical outcome. Conclusions: High expression of FOXP3 in the primary melanoma may be used as an additional independent prognostic marker for early tumour progression in patients with melanoma.